Mídia e identidade discursiva: a dialética idem x ipse na produção televisiva local - Stürmer, Adriana (2008)
This study analyzes the discursive action of media as an identity builder. Globalization and mediatization processes compose the context in which the relations of a free to air TV channel fits in and which content is defined by a broadcast programming that needs to articulate a flux made of national, regional and local broadcasting stations. From this programming, we have researched the production of short time insertion programs lasting no more than 90 seconds, broadcasted during the commercial breaks and supported by sponsors, called programetes in Portuguese. From the data researched in 2006, we could observe the existence of these programs in 5 from 11 broadcasting stations of Rede Brasil Sul de Televisão RBS TV, associated to Rede Globo, all of them locally produced e broadcasted exclusively to cities located away from the capital of Rio Grande do Sul State. This kind of program is considered by TV stations as a way to overcome the short time that can be destined to subjects of local interest, and at the same time it guarantees to the sponsors they area offering a unique kind of product. We have analyzed some short time insertion programs of RBS TV dos Vales located in the city of Santa Cruz do Sul -RS. The program we analyzed was Preserve o que é nosso (Preserve what is ours), which has been broadcasted since 2002 and has more than 40 editions so far. It is broadcasted during the commercial breaks of Globo Repórter (Fridays nights) and Domingão do Faustão programs (Sundays afternoons). This local media has an important role for the remembrance of the European immigration to Brazil from the XIX Century on. Besides that, the concept of narrative identity has been revealed as fundamental and also a way to keep identity alive. Idem-identity or sameness would be related to a substratum through which it would be possible to reidentify a person with himself/herself. Ipse-identity or selfhood secures the concept of permanence in time that happens through the continuous relation with others and it operates through identification with values, models, heroes, etc. The dialectics between sameness and selfhood is inserted in the notion of narrative identity. Narrative is considered a set of stories, registers and imagination, while the discourse is the act of this narrative. The data collected show that short time insertion programs consider the concept of preserving the memory of the former generations giving attention to aspects as conservation and recuperation of the architectural heritage and the narrative that is related to it. Short time insertion programs are lined up with informative and promotional genres and also with documentary and social merchandising subgenres. The discursivity analysis shows that the houses are structuring elements. Through its exposition, at least two perspectives can be cited. Focusing on the triumph of the immigrants who faced a new land with extreme difficulties would strengthen sameness because of the maintenance of the character which identifies a group as a whole. At the same time, regarding the permanence in time, it shows that future generations will be able to access the preserved architectural and cultural heritage, besides these generations are characterized by selfhood, the introduction of others in the constitution of their own identities.